COVID-19 classification using chest X-ray images: A framework of CNN-LSTM and improved max value moth flame optimization - Hamza, Ameer; Attique Khan, Muhammad; Wang, Shui-Hua; Alqahtani, Abdullah; Alsubai, Shtwai; Binbusayyis, Adel; Hussein, Hany S.; Martinetz, Thomas Markus; Alshazly, Hammam (Frontiers in Public Health, 2022)
Covid19 is a highly contagious disease that has claimed the lives of millions of people worldwide in the last two years. Because of the disease's rapid spread, it is critical to diagnose it at an early stage in order to reduce the rate of spread. The images of the lungs are used to diagnose this infection. In the last two years, many studies have been introduced to help with the diagnosis of Covid19 from chest X-Ray images. Because all researchers are looking for a quick method to diagnose this virus, deep learning-based computer controlled techniques are more suitable as a second opinion for radialogists. In this paper, we look at the issue of multisource fusion and redundant features. We proposed a CNN-LSTM and improved max value features optimization framework for Covid19 classification to address these issues. The original images are acquired and the contrast is increased using a combination of filtering algorithms in the proposed architecture. The dataset is then augmented to increase its size, which is then used to train two deep learning networks called Modified EfficientNet B0 and CNN-LSTM. Both networks are built from scratch and extract information from the deep layers. Following the extraction of features, serial based maximum value fusion technique is proposed to combine the best information of both deep models. However, a few redundant information is also noted; therefore, an improved max value based moth flame optimization algorithm is proposed. Through this algorithm, best features are selected and finally classified through machine learning classifiers. The experimental process was conducted on three publically available datasets and achived improved accuracy than the existing techniques. Moreover, the classifiers based comparison is also conducted and cubic support vector machine gives the better accuracy.